Qualitative Analyses of the Reasons Why Patients Do Not Attend Scheduled Inpatient Appointments in a Hospital in Guangzhou, China - Yang M; Xie J; Zhang H; Chen Y; Xie S; Peng R; Jia Y; Chen Y; Wang L (Dove Medical Press, 2020)
Mudi Yang,1,2 Jun Xie,2 Huan Zhang,2 Yingyong Chen,2 Shuo Xie,2 Rui Peng,2 Yu’e Jia,2 Yajing Chen,2 Lizi Wang1,2 1School of Nursing, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 2Admission Management Center of Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Lizi WangAdmission Management Center of Zhujiang Hospital, Southern Medical University, 253 Gongye Road M, Haizhu District, Guangzhou, Guangdong 510280, People’s Republic of ChinaTel/Fax +86 206 278 2038Email manbao99@126.comPurpose: Exploration of the reasons why people miss scheduled inpatient appointments from the perspectives of patients.Methods: Semi-structured interviews via telephone were conducted with patients who missed their inpatient appointments. Data were analyzed based on Colaizzi’s seven-step method.Results: Twenty-five patients and five dependents were enrolled. Three themes were identified: practical barriers, lack of knowledge about the disease, and negative emotional responses. Personal social obligations, state of illness, financial issues and long waiting times were the main practical barriers preventing patients from attending their inpatient appointment. Patients’ perceptions of feasible self-solving symptoms, readily believing people around them, and a blindly optimistic attitude towards disease contributed to their insufficient knowledge about the disease. Negative emotional responses (eg, sense of fear and lack of trust in physicians) had a detrimental effect on inpatient attendance.Conclusion: Three main factors contributed to non-attendance of inpatient appointments: practical barriers, lack of knowledge about disease, and negative emotional response. Our study provides new, valuable evidence on non-attendance of inpatient appointments in China. Our findings could offer meaningful insights into developing effective strategies to reduce non-attendance of inpatient appointments in other countries.Keywords: non-attendance, health-seeking behavior, medical appointment services, qualitative study, inpatient appointment